Educational development in a period of transition: the case of Kazakhstan - Rimantas, Ž.; Kusainov, A.; Yessenova, Kamchat; Sembaeva, A. (Farabi Journal of Social Sciences, 2021)
The development of education in the post-socialist space is one of the most interesting objects for comparative research. Countries that had similar or even identical education systems before the fall of the socialist regime can today serve as a research platform for testing modern theories of social development. According to modernization theory, the “underdeveloped” post-socialist countries had to catch up with their more “advanced” Western counterparts. Due to the fact that in all countries the goals of the reforms were similar, the expected result should have been more or less the same. However, despite the recommended reforms of Western consultants, different trajectories are observed in the educational system. Obviously, the prevailing tendencies in the educational system are divergence instead of convergence. According to the theory of dependence, the world is a single economic system, and countries, in turn, perform different roles and functions. On the example of Kazakhstan, we see that over 30 years of independence, the education system of independent Kazakhstan has received a worthy international recognition. During the years of Independence, a national model of education has been formed, aimed at improving the quality of training of human resources, meeting the needs of the individual, society and the state. A regulatory legal framework has been formed. The laws of the Republic of Kazakhstan “On education”, “On higher education”, “On science”, “On the rights of the child in the Republic of Kazakhstan”, “On the state educational accumulative system”, “On the commercialization of the results of scientific and (or) scientific and technical activities “,” On the status of a teacher “and others. Key words: Post-socialism, educational transformations, transitory period, theories of modernization and dependency.